Improvement of the extraction of carotenoids and capsaicinoids of chili pepper native (Capsicum baccatum), assisted with cellulolytic enzymes - Gamarra Mendoza, Norma Nélida (2020)
The production of cellulases of Aspergillus niger ATCC 10864 was carried out by fermentation in biofilms (FB). The extracts of cellulases were used to hydrolyze the cellulose of Capsicum baccatum “escabeche chili” fruit, for this the chili fruits were dehydrated and ground to a particle size < 0.045 mm. Then dry chili: cellulase was mixed and hydrolyzed under conditions of agitation, controlled time and temperature. The medium was filtered and the supernatant of the hydrolyzed chili cake was separated, the latter was dried at 10% humidity and leached with a mixture of hexane:acetone:ethanol to extract the carotenoids and capsaicinoids, which were quantified by HPLC. The extraction yield of oleoresin was five times higher compared to the conventional method; likewise in the T8 and T5 treatments, greater extraction of carotenoids and total capsaicinoids was achieved compared to the other treatments. The hydrolytic action of the cellulases, on the molecular structures of the cellulose of the red drop chili fruit, favored greater release of the carotenoids and total capsaicinoids compared to conventional methods.